Theoretical Aspects on the Cognitive Dimensions in the Personality of the Pathological Gambler: Array - Miu, Florian Viorel (New Trends in Psychology, 2020)
Ambling is a socially accepted form of entertainment, a way to spend part of free time, a way to have a financial surplus, but which can turn over time into a destructive form that occupies the entire psycho-social sphere of individual. The cognitive theory is a prominent approach, even dominant in understanding human behavior. It is based on the idea that mental processes play a decisive role in the processes of thinking, emotions and behavior. Regarding pathological gambling, cognitivist theory supports that pathological gamblers are guided by irrational, incorrect, or false beliefs about chance, probability, and random events. Classical cognitivist research suggests that the pathological player has difficulty applying the principle of event independence and random results when there is a financial incentive involved.